Porous carbon foams supported rGO-ppy//rGO for asymmteric supercapacitor device - El-yaqub, Balarabe; Wahid, Mohd Haniff; Zainal, Zulkarnain; Abdullah, Abdul Halim; Wan Ab Karim Ghani, Wan Azlina (Elsevier Ltd, 2025)
Porous carbon foams (PCF) doped with binary composite of rGO-ppy was prepared using a simple dip coating method with the use of a linker and used as compressible electrodes for the asymmetric supercapacitor (ASC). Porous carbon foams were fabricated from melamine foam by carbonization in a furnace at a temperature of 300 °C and the binary composite was synthesized using hydrothermal method. The electrode materials were characterized using XRD, XPS, FTIR, BET/BJH, Raman and FESEM to confirm it's structural, functional group, surface area, thermal stability and morphological characteristics. The stress–strain tests of the samples were conducted on an electronic universal testing machine and the porous carbon foams can withstand the stresses of 14.5, 17.9 and 30.0 KPa at 40 %, 60 % and 80 % strains respectively. The mechanical properties were further examined by repeating the compression release process for 200cycles at a maintained strain of 80 %. The fabricated PCF-rGO-ppy//rGO supercapacitor device exhibited high deformation tolerance, outstanding electrochemical behaviour and enhanced cycling stability due to the flexible and compressible skeleton of the PCF and high electrical conductivity of rGO and ppy. Finally, an ASC was fabricated using PCF-rGO-ppy as cathode and rGO as the anode which showed a specific capacitance of 328.91F/g at 0.5A/g, energy density of 29.234Wh/kg and power density of 4000 W/kg. Electrochemical impedance spectroscopy (EIS) studies showed that rGO and the porous carbon can effectively improve the charge-transfer rate from the low charge-transfer resistance (Rct) value. The fabricated electrode also showed an exceptional cycling stability of 98.89 % after 10,000 galvanostatic charge discharge (GCD) cycles.